Determinants of Global Trade Barriers: An Empirical Analysis of Cross-Country Variations Using a Comprehensive Trade Index - Soliman, Zied (Journal of Business and Economic Options, 2025)
This undertaking offers a comprehensive index for trade barriers of 130, using available tariff data. In the case of missing tariff information, import values that corresponded to the Harmonised System classification with 6 digits were retrieved from the UNCTAD TRAINS database to build similar indicators. After constructing the indices, a series of econometric methods, including bivariate analysis, multivariate estimation, and the analysis of variance (or ANOVA) models, are used to analyse cross-country differences and highlight the determinants of trade barrier differences within and across countries. The results show that the constructed Indices for trade barriers vary across countries, but that these do not necessarily show complete distinctions, but are rather systematically related to other characteristics such as per capita income, population size and national literacy levels. The results indicate that economic development, demographic characteristics, and human capital conditions determine the structure and strength of trade barriers across countries. The paper also uses developing countries as a reference case to illustrate the variations in calculating the trade barrier indices resulting from using different product classification levels. Furthermore, the study warns that the comparative rankings of two countries would not necessarily show differences in trade barriers associated with different industries because aggregate indices may obscure sector-level differences. Overall, the research adds to a better understanding of the differences between trade barriers across countries and the importance of being careful in interpreting cross-country comparisons, particularly if you are making evaluations of trade policy or industry and country-specific issues.